2011
DOI: 10.1002/tox.20760
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal toxicity of esbiothrin relationship with total antioxidant status andin vivogenotoxicity assessment in fish (Cyprinus carpio L., 1758) using the micronucleus test and comet assay

Abstract: Esbiothrin, synthetic pyrethroid with quick activity against insects, is widely used against household pests and in public health. Despite widespread use, data on ecotoxicity and genotoxic effects are extremely scarce. The aim of the present study is to evaluate the genotoxic potential of esbiothrin on a model fish species Cyprinus carpio L., 1758 (Pisces: Cyprinidae, koi) using the micronucleus test and comet assay in peripheral blood erythrocytes. Effects of two sublethal exposure concentrations on plasma to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 46 publications
2
7
0
Order By: Relevance
“…Nwani, Lakra, Nagpure, Kumar, Kushwaha and Srivastava () determined increased MN frequencies after exposure to 67, 134 and 201 μg L − 1 carbofuran for 24, 48, 72 and 96 h in freshwater air‐breathing fish Channa punctatus (mean weight 16.50 g). Esbiothrin exposure resulted in increased micronucleus frequencies in C. carpio exposed to sublethal concentrations of 5 and 10 μg L − 1 for 24, 48 and 72 h (Selvi, Çavas, Benli, Memmi, Çinkılıç, Sepici‐Dinçel, Vatan, Yılmaz, Sarıkaya, Zorlu & Erkoç ). Çavaş and Könen () reported high MN frequencies after exposure to domoic acid at a concentration of 1.5 and 10 μg g −1 of body weight.…”
Section: Discussionmentioning
confidence: 99%
“…Nwani, Lakra, Nagpure, Kumar, Kushwaha and Srivastava () determined increased MN frequencies after exposure to 67, 134 and 201 μg L − 1 carbofuran for 24, 48, 72 and 96 h in freshwater air‐breathing fish Channa punctatus (mean weight 16.50 g). Esbiothrin exposure resulted in increased micronucleus frequencies in C. carpio exposed to sublethal concentrations of 5 and 10 μg L − 1 for 24, 48 and 72 h (Selvi, Çavas, Benli, Memmi, Çinkılıç, Sepici‐Dinçel, Vatan, Yılmaz, Sarıkaya, Zorlu & Erkoç ). Çavaş and Könen () reported high MN frequencies after exposure to domoic acid at a concentration of 1.5 and 10 μg g −1 of body weight.…”
Section: Discussionmentioning
confidence: 99%
“…To date, many chemicals involved in the environment have identified in fish as genotoxic but there is no result of boron compounds. In the recent years, several studies have been reported by the Comet assay (Abd-Allah et al, 1999[ 1 ]; Andrade et al, 2004[ 6 ][ 5 ]; Buschini et al, 2004[ 10 ]; Jha, 2008[ 24 ]; Frenzilli et al, 2009[ 16 ]) to evaluated the genotoxic agents in various species of fish (Sumathi et al, 2001[ 45 ]; Akcha et al, 2003[ 4 ]; Cavaş and Konen, 2007[ 12 ]; Simoniello et al, 2009[ 43 ]; Kumar et al, 2010[ 28 ]; Scalon et al, 2010[ 39 ]; Yang et al, 2010[ 57 ]; Cavaş, 2011[ 11 ]; Nwani et al, 2011[ 33 ]; Pandey et al, 2011[ 36 ]; Nagarani et al, 2012[ 32 ]; Selvi et al, 2013[ 42 ]) and aquatic invertebrates which can serve as excellent source of material for genotoxic, mutagenic and carcinogenic studies on environment.…”
Section: Resultsmentioning
confidence: 99%
“…The DNA damage measured by DNA strand breakage performs as a reliable indicator of genotoxicity. Several studies have shown that the comet assay is so sensitive, rapid and extensively used methods in detection genotoxicity of chemicals under field and laboratory conditions (Abd-Allah et al, 1999[ 1 ]; Cavaş and Konen, 2007[ 12 ]; Kumar et al, 2010[ 28 ]; Cavaş, 2011[ 11 ]; Nwani et al, 2011[ 33 ]; Pandey et al, 2011[ 36 ]; Nagarani et al, 2012[ 32 ]; Selvi et al, 2013[ 42 ]) in fish.…”
Section: Introductionmentioning
confidence: 99%
“…The MNi test measures a small subset of unrepaired DNA strand breaks, whereas the comet assay measures strand breaks and labile sites that may be removed subsequently by the DNA repair system, both studies complement each other and their methodology is easy and does not require sophisticated equipment (Ko nca et al, 2003;Heuser et al, 2008). On the other hand, certain genotoxic agents also induce cytotoxicity (Selvi et al, 2013), defined as the pre-lethal changes and events which occur in cells prior to necrosis (Vasquez, 2012). Lesions to DNA and inefficient repair mechanisms are crucial in the un-leashing of apoptosis (Roos and Kaina, 2006), which is a fundamental biochemical pathway of cellular death characterized by diverse morphologic changes and has a major role in the maintenance of tissue homeostasis (Simoes et al, 2013).…”
Section: Introductionmentioning
confidence: 99%